1975
DOI: 10.1139/m75-167
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface protein of Salmonella typhimurium

Abstract: Lactoperoxidase-catalyzed radioiodination with Na125I was performed both on intact Salmonella typhimurium 1195 and on ghost membrane isolated from the same bacterial strain. Ghost membrane was also prepared from radioiodinated whole bacteria. The labelled proteins from both these ghost membrane preparations were compared by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate to identify the cell surface proteinmfrom the results obtained it was concluded that one major protein with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our results indicate that although the cell envelope components of V. cholerae are predominantly murine B-cell mitogens, properties like toxicity and adjuvanticity are only possessed by LPS. It is believed that the lipid A moiety of LPS, which remains buried in the cell membrane (Shands, 1973;Kabir et al, 1978), mediates most of these biological properties (Luderitz et al, 1973). Hence, in the spheroplasts the lipid moiety of LPS is not available for interaction with other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that although the cell envelope components of V. cholerae are predominantly murine B-cell mitogens, properties like toxicity and adjuvanticity are only possessed by LPS. It is believed that the lipid A moiety of LPS, which remains buried in the cell membrane (Shands, 1973;Kabir et al, 1978), mediates most of these biological properties (Luderitz et al, 1973). Hence, in the spheroplasts the lipid moiety of LPS is not available for interaction with other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The outer membrane contains lipopolysaccharide (LPS), protein and lipid, while the inner or cytoplasmic membrane consists of protein and lipid. In Gram-negative bacteria, both LPS and protein moieties remain exposed on the cell surface (Shands, 1966;Kabir, 1975;Rittenhouse et al, 1973) and it is most likely that these components play a role in the interaction of the bacterium and the host during infection. Among the various cell envelope components of Gram-negative bacteria, LPS has received most attention and has been found to have a variety of immunological effects in the susceptible host (Kass & Wolff, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…However, Lambert and Booth (20) reported that there are only four surface exposed proteins on Pseudomonas aeruginosa, an organism which also secretes numerous proteins. Their study, as well as other studies (8,15,31,33), did not, however, specify the efficiency of iodination or the amount of radiolabeled material examined by SDS-PAGE. In some cases it is clear that little radiolabeled material was analyzed.…”
mentioning
confidence: 92%
“…These studies and others (16,17,34) indicate that the outer membrane of V. cholerae is a complex structure containing many proteins.Proteins exposed on the bacterial surface are likely to contribute to colonization of the host, and improved knowledge of the surface proteins should further our understanding of their role in colonization. The surface proteins of several bacterial species have been identified by iodination with membrane-impermeable enzymes (15,20,29,31) or the water-insoluble reagent, 1,3,4,6-tetrachloro-3,6-diphenylglycouril (Iodogen) (33). We used lodogen-coated vessels and a covalently immobilized catalyst (lodo-beads) to radioiodinate whole cells and isolated outer membrane of V. cholerae.…”
mentioning
confidence: 99%
See 1 more Smart Citation